Constitutional Principles of Contractual Representation in Ukraine: Problems of Theory and Practice - Цюра, Вадим Васильович; Цюра, В. В.; Цюра, Вадим Васильевич; Tsiura, Vadym V.; Сулейманова, Сусанна Рефатівна; Сулейманова, С. Р.; Сулейманова, Сусанна Рефатовна; Suleimanova, Susanna R.; Сотула, Олександр Сергійович; Сотула, О. С.; Сотула, Адександр Сергеевич; Sotula, Oleksandr S.; et al. (ASERS Publishing System, 2019)
The research is devoted to the issue of the nature and essence of the contractual representation as a legal relationship and a constitutional principle.The current understanding of the institution of representation in the context of the provisions of the Code of Civil Procedure of Ukraine and the Civil Code of Ukraine is ambiguous and this problem needs to be solved. In order to determine the true meaning of the legal institute of representation, the authors of the article made an attempt to study it through the lens of the norms of the current constitution of Ukraine.The methods of scientific research, used by the authors are the analysis, the synthesis, the deduction and induction,the comparison-legal method. All these methods in their convergence made it possible to find out the current state of the existing legislation and legal doctrine in the context of contractual representation and to offer the authors’ own vision of directions of improvement of the studied legal institute.In the result of the study the authors made a conclusion that a contractual representation is a kind of representation, arising out of a contract or other act that underlies the will of the person represented (the principal) and the person representing (the attorney) and the agreement between them. It is important for both the practice of law and the theory of law that the understanding of the essence of the said institute and the approaches to regulating relations of representation in the Civil Code and in the Civil Procedure Code be the same.

Дослідження присвячено питанню природі та сутності договірного представництва як правовідношення та конституційного принципу. Сучасне розуміння інституту представництва в контексті положень ГПК України та ЦПК України. Кодекс України неоднозначний, і ця проблема потребує вирішення. З метою визначення справжнього змісту правового інституту представництва автори статті зробили спробу дослідити його через призму норм чинної Конституції України. Методами наукового дослідження, якими користуються автори, є аналіз, синтез, дедукція та індукція, порівняльно-правовий метод. Усі ці методи у своїй конвергенції дозволили з’ясувати сучасний стан чинного законодавства та правової доктрини в контексті договірного представництва та запропонувати власне бачення авторів напрямів удосконалення досліджуваного правового інституту. У дослідженні автори зробили висновок про те, що договірне представництво є різновидом представництва, що випливає з договору чи іншої дії, що лежить в основі волі особи, яку представляють (довірителя) та особи, яка представляє (повіреного), та угоди між ними. Як для юридичної практики, так і для теорії права важливо, щоб розуміння сутності зазначеного інституту та підходів до регулювання відносин представництва у ГК та у ЦПК були однаковими.
Tsiura V. Constitutional Principles of Contractual Representation in Ukraine: Problems of Theory and Practice / V. Tsiura, S. Suleimanova, O. Sotula, V. Panasiuk, V. Dobrovolska // Journal of Advanced Research in Law and Economics. - Vol. 10. - № 3. - ASERS Publishing System, 2019. - Р. 948-953.
Keywords: contractual representation; legal relations; the institution of representation; power of attorney; сivil legal relations; constitutional principles; договірне представництво; правовідносини; інститут представництва; довіреність; цивільні правовідносини; конституційні принципи; Research Subject Categories::LAW/JURISPRUDENCE